2021
DOI: 10.1088/1755-1315/782/4/042012
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and condition factor of signal barb fish (Labiobarbus festivus) at the Tasik River, South Labuhanbatu Regency, Sumatra Utara Province

Abstract: The purpose of this study was to determine the morphometric and meristic characteristics, growth of Signal barb fish in the Tasik river. The method used in this research is a survey method. Morphometric characteristics of Signal barb fish Bodyweight (BW) ranges from 4-73 gr, Total Length (TL), Standard Length 6.3-15.5 mm (SL), Head Length (HL) 1.8-2.5, Snout Length (SL) 0.5, Dorsal Fin Height (DFH) 2.3, Dorsal Fin Length (DFL) 3-7, Eye Diameter (EM) 0.8, Tail Trunk Height (TTH) 0.8-1.8, Body Height (BH) 2-4.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…The type of base can modify the current velocity differential between rivers, the river's width, and the existence of barriers to River currents (Djumanto et al 2013). Similarly, these factors support a diverse array of fish species in the Wampu, Bahorok, and Batangtoru rivers (Muhtadi et al 2017;Desrita et al 2018;Desrita et al 2020) Hemibagrus and Kryptopterus are bottom fish, which can be seen from the body shape, which is flat compressed (Hemibagrus), whereas Anabas, Barbonymus (Nurfadillah et al 2019;Desrita et al 2021c), and Pristolepis are mid-to deep-water fish, and Cyclocheleichtys, Rasbora, Barbichthys, and Labiobarbus are surface fish (Desrita et al 2021b). The only shrimp found in Labuhanbatu rivers is the gigantic prawn (M. rosenbergii), located in the Barumun River.…”
Section: Distributionmentioning
confidence: 91%
“…The type of base can modify the current velocity differential between rivers, the river's width, and the existence of barriers to River currents (Djumanto et al 2013). Similarly, these factors support a diverse array of fish species in the Wampu, Bahorok, and Batangtoru rivers (Muhtadi et al 2017;Desrita et al 2018;Desrita et al 2020) Hemibagrus and Kryptopterus are bottom fish, which can be seen from the body shape, which is flat compressed (Hemibagrus), whereas Anabas, Barbonymus (Nurfadillah et al 2019;Desrita et al 2021c), and Pristolepis are mid-to deep-water fish, and Cyclocheleichtys, Rasbora, Barbichthys, and Labiobarbus are surface fish (Desrita et al 2021b). The only shrimp found in Labuhanbatu rivers is the gigantic prawn (M. rosenbergii), located in the Barumun River.…”
Section: Distributionmentioning
confidence: 91%
“…Nonetheless, previous morphometric characterisation of this fish species collected from the Sumatra Utara Province, Indonesia revealed much smaller size. Desrita et al, (2021) reported weight ranges from 4-73 gram and standard length between 0.63-1.55 cm [17]. Meanwhile, Puntoplites bulu (P. bulu) or Tengalan is the biggest fish species identified with its weight approximately tripled the signal barb.…”
Section: Physical Characteristicsmentioning
confidence: 99%